Simulation Analysis on Eddy Current Braking Force of High-speed Maglev Train - Mingxing WANG; Ping CHEN; Changfeng YANG; Wenqi YUAN; Lei YANG; Hongqing ZHU; Zhenwei DONG (机车电传动)
Based on Faraday's law of electromagnetic induction, the mathematical model of eddy current braking force was established, and the factors influencing the eddy current braking force were analyzed. The tangential braking force and normal suction force of the eddy current brake of TR08 high-speed maglev train in Germany under the air gaps of 8 mm, 11 mm, 15 mm and 19 mm were calculated by using the finite element simulation analysis method. The simulation results were consistent with the test data, which met the requirements of train safety braking deceleration.